Design of flux‐weakening space vector control algorithms for permanent magnet brushless DC machines on suitable synchronous reference frames. Issue 4 (4th December 2019) - Serpi, Alessandro; Porru, Mario; Fois, Giuseppe; Damiano, Alfonso
Abstract : The design of space vector control (SVC) systems suitable for flux‐weakening operation of permanent magnet brushless DC machines (PMBDCMs) is presented in this study. The proposed design approach enables overcoming the critical issues arising from the non‐linearities of PMBDCM voltage and torque equations; these issues derive from the trapezoidal shapes of back‐emfs and affect PMBDCM constraint management significantly. The SVCs presented in this study have been developed within two different synchronous reference frames, both of which enable distinguishing torque and demagnetising current components clearly. Therefore, reference torque current component is determined in accordance with PMBDCM torque demand, while reference demagnetising current component is computed through a voltage follower PI regulator, which processes the voltage deficit detected on the DC‐link. In this regard, a novel synchronous reference frame is proposed in this study, which improves PMBDCM constraint management and results into a wider constant‐power speed range, but at the cost of some torque ripple. The enhanced performances achievable by SVC approaches are highlighted by numerical simulations, which regard the comparison among the SVCs and an SVC with no flux‐weakening capability, at different operating conditions.